2014
DOI: 10.1142/s0218195914600127
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Point Labeling Is Strongly Pspace-Complete

Abstract: An important but strongly NP-hard problem in automated cartography is how to best place textual labels for point features on a static map. We examine the complexity of various generalizations of this problem for dynamic and/or interactive maps. Specifically, we show that it is strongly PSPACE-complete to decide whether there is a smooth dynamic labeling (function from time to static labelings) when the points move, when points are added and removed, or when the user pans, rotates, and/or zooms their view of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…If this was not the case, then the prefix [−M, 0] or the suffix [l 1 , l 1 + M] of K cannot belong to the activity of K . Further, for the interval [0, l 1 ] we obtain less than 2 3 M weight in total, because at most two labels can be active at the same time and l 1 < M 3 . Thus, we obtain W Φ < M + 2 3 M < 2M .…”
Section: Complexity Of K-restrictedmaxtotal In Am3mentioning
confidence: 99%
See 2 more Smart Citations
“…If this was not the case, then the prefix [−M, 0] or the suffix [l 1 , l 1 + M] of K cannot belong to the activity of K . Further, for the interval [0, l 1 ] we obtain less than 2 3 M weight in total, because at most two labels can be active at the same time and l 1 < M 3 . Thus, we obtain W Φ < M + 2 3 M < 2M .…”
Section: Complexity Of K-restrictedmaxtotal In Am3mentioning
confidence: 99%
“…Further, for the interval [0, l 1 ] we obtain less than 2 3 M weight in total, because at most two labels can be active at the same time and l 1 < M 3 . Thus, we obtain W Φ < M + 2 3 M < 2M . On the other hand, because of l 2 ≥ 2M and W Φ ≥ W , we have W Φ ≥ 2M , which is a contradiction.…”
Section: Complexity Of K-restrictedmaxtotal In Am3mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we note that the dynamic problem has attracted attention in the past decade due to its increasing importance in several applications such as personal mapping systems. We refer to [2,[10][11][12]16,21,22] for problems with static sites and a dynamic map, and Buchin and Gerrits [3] for their hardness results. De Berg and Gerrits [7], on the other hand, discussed a trade-off between label speed and label overlap.…”
Section: Related Workmentioning
confidence: 99%
“…They presented a sophisticated heuristic for finding a reasonable trade-off between label speed and label overlap. Finally, Buchin and Gerrits [3] showed that dynamic point labeling is strongly PSPACE-complete. The corresponding viewport of the camera.…”
Section: Related Workmentioning
confidence: 99%